An Investigation of the Pre-Services Teachers' Ability of Using Multiple Representations in Problem-solving Success: The Case of Definite Integral - (:unkn) unknown (EDAM, 2010)
Using different representations and having flexibility of transition between representations throughout the definite integral problem-solving process are thought to be effective on the development of conceptual understanding and students' performance. The study aims at considering the effects of representations used in the definite integral on pre-services teachers' problem-solving achievement. The research is a case study having qualitative paradigm. Within the context, a case study with 45 pre-services teachers from a mathematics teaching department in a state university has been conducted. This study uses multi-method approach to collect the data which are qualitative. The data were analyzed and interpreted through classification method and descriptive statistical techniques. The findings indicate that the skills of pre-services teachers in using multiple representations within the process of solving certain definite integral problems were not sufficient as required. It was specified that the candidates trying to solve problems with the domination of merely one representation were weak in terms of the transition of representation skills and they were in low level in terms problem-solving. After discussing the findings of the study in the light of the literature some suggestions are given for increasing the problem-solving success.
Keywords: Definite Integral; Multiple Representations; Problem Solving Achievement